Impact of a peri‐operative quality improvement programme on postoperative pulmonary complications. (4th January 2017) - Moore, J. A.; Conway, D. H.; Thomas, N.; Cummings, D.; Atkinson, D.
Summary: Postoperative pulmonary complications are common, with a reported incidence of 2–40%, and are associated with adverse outcomes that include death, longer hospital stay and reduced long‐term survival. Enhanced recovery is now a standard of care for patients undergoing elective major surgery. Despite the high prevalence of pulmonary complications in this population, few elements of enhanced recovery specifically address reducing these complications. In 2013, a prevalence audit confirmed a postoperative pulmonary complication rate of 16/83 (19.3%) in patients undergoing elective major surgery who were admitted to critical care postoperatively. A quality improvement team developed and implemented ERAS+, an innovative model of peri‐operative care combining elements of enhanced recovery with specific measures aimed at reducing pulmonary complications. ERAS+ was introduced in June 2014, with full implementation in September 2014. Patients were screened during full ERAS+ implementation and again one year following implementation. Following ERAS+ implementation, postoperative pulmonary complications reduced to 24/228 (10.5%). Sustained improvement was evident one year after implementation, with a pulmonary complication rate of 16/183 (8.7%). Median (IQR [range]) length of hospital stay one year after implementation of ERAS+ also improved from 12 (9–15 [4‐101]) to 9 (5.5–10.5 [3‐81]) days. The ERAS+ pathway is applicable to patients undergoing elective major surgery and appears effective in reducing postoperative pulmonary complications. Abstract : ☛ CPD available athttp://www.learnataagbi.org